Translation into portuguese of a set of questionnaires designed to evaluate the impact of using a telepresence robot during postoperative ward rounds - KRISTEM,LEONARDO (2022)
ABSTRACT Introduction: the use of telepresence grows with the advancement of technology integration into medical practice. Regarding surgery, effective distance communication can translate into better perioperative care. Though, the patients’ perception about this modality needs to be critically evaluated. Structured questionnaires using objective scales are the instruments of choice for measuring subjective aspects. However, there are no such questionnaires available in Portuguese. Our objective was, thus, translate and adapt into Portuguese a specific questionnaire evaluating the use of telepresence robots during post-operatory ward rounds. Methods: search on PubMed and selection of a set of validated questionnaires in English, translation into Portuguese according to the principles of good practice for the translation and cultural adaptation process for patient-reported outcomes measures. The original author approved the final version. Results: three questionnaires that assess ward rounds assisted by a telepresence robot were translated. Questionnaires are directed to the patient who receives the visit via telepresence or face-to-face visit and to the medical team accompanying the visit. The questionnaires use the Likert scale and contain thirteen questions that address 5 spheres: Communication; Dignity and Confidentiality; Contents; Time; General Impressions. Conclusions: this is the first instrument in Portuguese designed to assess the impression of patients and professionals involved in ward rounds using a telepresence robot. It has the potential to be used in clinical studies involving the use of this technology in care.